Sports Psychology II - Think your way to success - Karageorghis, C.; Crust, L.; Petruzzi, J.; Lane, H.; Lane, A. (Peak Performance, 2007)
Motivation: The first chapter takes a look at the dynamics of motivation, without which there is little hope for sporting success.